Baseline survey of root-associated microbes of Taxus chinensis (Pilger) Rehd. - Qian Zhang (PLoS ONE, 2015)
Taxol (paclitaxel) a diterpenoid is one of the most effective anticancer drugs identified. Biosynthesis of taxol was considered restricted to the Taxus genera until Stierle et al. discovered that an endophytic fungus isolated from Taxus brevifolia could independently synthesize taxol. Little is known about the mechanism of taxol biosynthesis in microbes, but it has been speculated that its biosynthesis may differ from plants. The microbiome from the roots of Taxus chinensis have been extensively investigated with culture-dependent methods to identify taxol synthesizing microbes, but not using culture independent methods.,Using bar-coded high-throughput sequencing in combination with a metagenomics approach, we surveyed the microbial diversity and gene composition of the root-associated microbiomefrom Taxus chinensis (Pilger) Rehd. High-throughput amplicon sequencing revealed 187 fungal OTUs which is higher than any previously reported fungal number identified with the culture-dependent method, suggesting that T. chinensis roots harbor novel and diverse fungi. Some operational taxonomic units (OTU) identified were identical to reported microbe strains possessing the ability to synthesis taxol and several genes previously associated with taxol biosynthesis were identified through metagenomics analysis.